An Overview of Agricultural Mechanization in Nepal - Shrestha, Shreemat (Kathmandu University Journal of Science, Engineering and Technology, 2022)
Increased migration of the youth from Nepal has created a demand for mechanization in Nepalese agriculture. The systematic agricultural mechanization can lead towards the sustainable agricultural commercialization for a prosperous Nepal. This paper analyzes the efforts, status, and policies related to agricultural mechanization and recommends policy reforms to align with the new constitution of the Federal Republic of Nepal, institutional capacity building, business development, favoring local production of agricultural machinery, promotion of custom hiring in business model, capacity development, promotion of women-friendly technologies, equitable agricultural mechanization program, and an integrated effort for sustainable agricultural mechanization through a public-private partnership model.